Development of Google Sites-Based Teaching Materials for Mathematics Subjects with Addie Model - Komariah Komariah; Rufii Rufii; Ujang Rohman (Green Publisher Indonesia, 2024)
The purpose of this development is to produce Google sites-Based Teaching Materials on Mathematics subjects in the form of E-Books. As a learning support medium, this E-Book is equipped with the Google Sites platform which is expected to improve the quality of the learning process where there is an increase in learning motivation in Mathematics subjects and will ultimately improve student learning outcomes. The development model used in the development of interactive learning multimedia is the ADDIE model. The ADDIE model stands for five stages of the development process, namely Analysis, Design, Develop, Implement, & Evaluate. The development process involves subject content experts, learning design experts and learning media experts to provide feedback and input on improvement. In addition, mathematics teachers. The result of this development research is that this Google sites-Based Teaching Material Product has a level of material feasibility, learning design feasibility, and learning media feasibility. Meanwhile, the level of small group trials and field trials with qualifications is very feasible and does not need to be revised.